Analisis Semantik Ujaran Kebencian di Kolom Komentar Instagram @Ahmadsahroni88 - Gardian Izzan Pancakusuma; Muhammad Key Arsha Ramadhan; Ikrar Nusa Bhakti; Fallujah Fallujah (SOSMANIORA: Jurnal Ilmu Sosial dan Humaniora, 2025)
Social media has become a space where various forms of public expression appear, including the use of language that reflects verbal aggression. This study aims to identify the forms of hate speech directed at Ahmad Sahroni in the Instagram comment section and to analyze the lexical and connotative meanings embedded in these expressions. Using a descriptive qualitative approach, the data were collected from five posts with the highest engagement, yielding 465 comments selected for analysis. The data were examined through a semantic framework to categorize hate-speech referents into nine groups and interpret the meanings based on their contextual use. The findings indicate that references related to conditions and body parts appear most frequently, followed by objects, kinship terms, professions, animals, activities, supernatural beings, and calls to action. The lexical and connotative analysis reveals that many expressions undergo a shift from their basic meanings toward evaluative meanings that reinforce verbal aggression. This study concludes that hate speech on social media functions not only as negative expression but also as a form of symbolic violence that shapes public perception of political figures.